Battle-Wise : Seeking Time-Information Superiority in Networked Warfare - Gompert, David C. ; Lachow, Irving and Perkins, Justin 1975- (Rawalpindi, Pakistan Services Books Club, 2014)
As the world careens into the 21st century, the capacity and means by which the American Armed Forces defend their nation are entering a paradigm-breaking transition period. Previous transitions have been driven by the technologies of weapons and their platforms: from sail, to boiler, to turbine; from foot, to horse, to vehicle; from balloon, to manned aircraft, to unmanned aircraft. This is not so in the 21st century. We need to reset our (3z(Bwarfighting gyro,(3y (Bso to speak. To this end, taking the information revolution as a starting point, Battle-Wise argues that only by strengthening the relationship between information technology and brain matter will the U.S. military enhance its ability to outsmart and outfight future adversaries. We certainly have had our challenges in recent military operations. Despite the exceptional heroism, courage, and intellect of today$1 (Bs young military members, we need to reformulate the manner by which we prepare them. For decades we have given them the best weapons systems our country could produce. The authors believe, as I do, that the time has come to augment weapons systems and information networks with the intellectual tools that will enable them to gain and maintain cognitive superiority and thus turn the tables on our clever and nimble adversaries. Only by developing battle-wise soldiers$1 (Ba daunting, but critically important effort on the part of our military leadership$1 (Bcan we expect to avoid the (3z(Bsecond kick of a mule.(3ys
Includes Glossary
Keywords: United States -- Computer Networks -- Information Warfare